2002
DOI: 10.1177/03635465020300021901
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Knee Kinetics between Male and Female Recreational Athletes in Stop-Jump Tasks

Abstract: We compared the knee kinetics of 10 male and 10 female recreational athletes (aged 19 to 25 years) performing forward, vertical, and backward stop-jump tasks. Three-dimensional videography and force plate data were used to record the subjects' performance of the three stop-jump tasks, and an inverse dynamic procedure was used to estimate the knee joint resultant forces and moments. Women exhibited greater proximal anterior shear force than did men during the landing phase. All subjects exhibited greater proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
302
7
17

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(351 citation statements)
references
References 28 publications
25
302
7
17
Order By: Relevance
“…Soccer-specific motions such as planting and pivoting, deceleration, and landing from a jump have all been identified as mechanisms of noncontact ACL injuries [1]. Recent studies have shown gender differences in lower-extremity kinematics and kinetics in athletic tasks [1,2]. Numerous authors have identified valgus collapse of the knee as the common body position in noncontact ACL injuries [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soccer-specific motions such as planting and pivoting, deceleration, and landing from a jump have all been identified as mechanisms of noncontact ACL injuries [1]. Recent studies have shown gender differences in lower-extremity kinematics and kinetics in athletic tasks [1,2]. Numerous authors have identified valgus collapse of the knee as the common body position in noncontact ACL injuries [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that collegiate and high school female soccer athletes are at a greater risk for tearing the anterior cruciate ligament (ACL) as compared to their male counterparts. Numerous papers have established that women cut and land with their knees in valgus, placing their knees at risk for injury [1][2][3][4]. Descriptive data exist for physical characteristics of elite male soccer players [5][6][7]; however, there is no published information regarding the musculoskeletal characteristics of elite female soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Sagittal plane mechanisms for non-contact ACL in jury have been proposed previously for sports move ments (Chappell et al, 2002;DeMorat et al, 2004;Griffin et al, 2000). Such postulates are based on the fact that the landing phase of these movements typically incorporates large quadriceps force at relatively small flexion angles, a combination known to induce anterior force on the tibia (Durselen et al, 1995;Pandy and Shel bourne, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Such postulates are based on the fact that the landing phase of these movements typically incorporates large quadriceps force at relatively small flexion angles, a combination known to induce anterior force on the tibia (Durselen et al, 1995;Pandy and Shel bourne, 1997). Women are often observed to perform these movements with less knee flexion than males (Chappell et al, 2002;Malinzak et al, 2001), which is thus viewed as a likely contributor to their increased risk of ACL injury (Colby et al, 2000;Griffin et al, 2000;Lephart et al, 2002). The neuromuscular control and strength ratio of the hamstrings and quadriceps are also viewed as important components of a sagittal plane in jury mechanism (Colby et al, 2000;Griffin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Single limb balance can be progressed by time or numbers of repetitions of the contralateral extremity movements. These balance exercises can be progressed by having the athlete perform balance techniques in increasing degrees of knee flexion which may also have a protective effect as activities in knee flexion may limit exposure to excessive anterior tibial shear loads that may overload graft tissue while performance of dynamic tasks [88][89][90]. Increased progression of single limb balance can include balance with eyes closed, progressing to the entire balance sequence being done on a labile surface.…”
Section: Phase Iv: Postoperative 3 Months-6 Monthsmentioning
confidence: 99%